BIOMIMETIC CONTROL OF CRYSTAL ASSEMBLY BY GROWTH IN AN ORGANIC HYDROGEL NETWORK - Grassmann O.; Neder R.B.; Putnis A.; Lobmann P. (My University, 2003)
Calcite aggregates are mineralized in an organic poly-acrylamide hydrogel using a counter diffusion arrangement. The particles obtained show a characteristic pseudo-octahedral morphology, which is unexpected for calcite crystals. Scanning and transmission electron microscopy reveal a microstructure composed of individual highly aligned calcite crystallites. Although the aggregates consist of independent crystallites, the X-ray diffraction patterns suggest calcite single crystals. By analogy with some biominerals, the inorganic assembly is intergrown with an organic hydrogel network. A specific model is proposed for growth of the aggregate.[PUBLICATION ABSTRACT]
Keywords: MINERALOGY; CALCIUM; CRYSTALS